(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
The aim of the article is to address the different production strategies and formal solutions proposed by two European films by German-Turkish directors, Auf der anderen Seite (The Edge of Heaven, Fatih Akin, 2007), and Almanya: Willkommen in Deutschland (Almanya: Welcome to Germany, Yasemin and Nesrin Samdereli, 2011). The article will analyze the role of the spatial configurations and the temporal fragmentations in the representation of cultural conflicts and problematic identities. Both narratives address migration and border crossing issues, exploring the contemporary relations between (neutral) Germany and (exotic) Turkey. However, the approaches of the two films to these issues are very different, also because of the context of production and distribution. The analysis of these films will therefore be conducted in relation to the European cinematographic market, spatial-temporal configurations, and border thinking. It will be shown how European cinema responds to deep changes on imaginary, economic, and social levels, representing geopolitical mutations through narrative, formal, and productive choices.